2008
DOI: 10.24297/jac.v4i1.956
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Zinc and Phytate Interrelationships in Four Lesser-Known African Seeds Processed into Food Condiments

Abstract: The calcium (Ca), zinc (Zn) and phytate contents of raw, boiled, and boiled plus 72 h fermented samples of four lesser-known African seeds – Citrullus colocynthis, Cucumeropsis edulis, Ricinus communis  and Prosopis africana – locally used for production of condiments in Nigeria were evaluated. Zinc bioavailability of the samples were also estimated using molar ratios per kg dry weight of [phytate]:[Zn], [Ca]:[phytate] and [phytate][Ca]:[Zn]. The levels of phytate, Zn and Ca of the raw seed samples varied from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Our results proved that the combined processes of germination and fermentation of sorghum into kunu-zaki significantly (p<0.05) reduced the phytate/Fe and phytate/Zn molar ratios of sorghum to values (9.35 ± 0.05 and 6.45 ± 0.05, respectively) within the acceptable limit. The above observations re-enforce previous results that showed that the bioavailability of Zn and Fe in cereals and legumes are low but are generally improved by various processing techniques [7,8,23]. Meanwhile, [24] suggested that the solubility of phytate and the proportion of Zn bound in a mineral complex with phytate in the intestine depend on the levels of Ca.…”
Section: Phytochemical Raw Sorghum Raw Potato Germinated Sorghumsupporting
confidence: 88%
See 4 more Smart Citations
“…Our results proved that the combined processes of germination and fermentation of sorghum into kunu-zaki significantly (p<0.05) reduced the phytate/Fe and phytate/Zn molar ratios of sorghum to values (9.35 ± 0.05 and 6.45 ± 0.05, respectively) within the acceptable limit. The above observations re-enforce previous results that showed that the bioavailability of Zn and Fe in cereals and legumes are low but are generally improved by various processing techniques [7,8,23]. Meanwhile, [24] suggested that the solubility of phytate and the proportion of Zn bound in a mineral complex with phytate in the intestine depend on the levels of Ca.…”
Section: Phytochemical Raw Sorghum Raw Potato Germinated Sorghumsupporting
confidence: 88%
“…3 The computed mineral ratio of the samples are shown in Table 4. The Ca/P ratio was generally lower than 0.5 which was reported to be the minimum ratio required for favourable absorption of Ca in the intestine [8]. Calcium is an important constituent of body fluids and is required along with phosphorus for bone formation.…”
Section: Phytochemical Raw Sorghum Raw Potato Germinated Sorghummentioning
confidence: 99%
See 3 more Smart Citations